Milk somatic cell count, composition and yield of multi-breed dairy cattle in Ethiopia - Chernet, T.F.; Okeyo Mwai, Ally; Meseret, Selam; Negussie, E.; Mrode, Raphael A.; Tarekegn, G.M.; Edea, Z.; Gebreyohanes, Gebregziabher; Ekine-Dzivenu, Chinyere C.; Tera, A.; Tessema, T.S. (Informa UK Limited, 2024)
Mastitis is highly prevalent and causes significant economic loss in the Ethiopian dairy industry. An important aspect of monitoring dairy cow health and milk quality is understanding somatic cell count (SCC), composition and milk yield. This study aimed to evaluate milk SCC, composition, yield, and factors associated with the quality traits of Ethiopian dairy farms. A total of 3269 milk samples were collected from 1719 cows across 201 herds. The overall means and standard deviations of loge-transformed somatic cell score (SCS), fat, protein, lactose, and test day milk yield were 12.39 ± 1.61 cells/mL, 2.68 ± 1.71%, 3.17 ± 0.24%, 4.75 ± 0.36%, and 10.45 ± 5.04 litres, respectively. The results showed that 40.7% of the analysed milk samples had the SCC class ≤ 200x103 cells/mL. SCS was negatively correlated with milk yield and composition but moderately positively correlated with electrical conductivity (r = 0.41). Lactation stage, breed, parity, herd size and altitude significantly influenced most milk parameters, except fat content, which was unaffected by parity (p > 0.05). In conclusion, the highest SCS was recorded in this study. An increase in SCS negatively affects both milk yield and composition. Therefore, breed selection and herd management should focus on reducing the SCC to improve milk yield and quality.